Supplementary material: Annex A. Hermanson, et al. 2023, The production of smalt, and other cobalt compounds at the Blaafarveværket, Modum, Norway, in the 18th and 19th centuries. - Shortland, Andrew J. (Cranfield University, 2022)
The production of smalt, and other cobalt compounds at the Blaafarveværket, Modum, Norway, in the 18th and 19th centuries. This is a list of 82 samples in small glass vials, retained by the BCW Museum, but originally in the collection of the NorwegianUniversity of Science andTechnology. Samples for the paper were selected from here.
Keywords: 'supplementary materials'; 'sample list'; 'archive'